The Effect of Special Exercises to Develop Some Physical and Skill Capabilities Using Basketball Auxiliary Materials (3 vs 3) for Youth Players (Medico Legal Update, 2020)
For weight lifting exercises, these exercises work to develop (the explosive strength of the arms) and (theforce characterized by speed, and the bearing strength of the two legs) as well as developing the skill ofshooting by jumping with two point and through the researcher’s follow-up to the matches, he found thatmany young players lose a lot of physical and skill capabilities with the passage of time, especially in thelast minutes of the game. Due to the lack of interest in some requirements of the training process, including(the explosive strength of the arms) and (the force distinguished by the speed and the bearing strength of thetwo legs) in addition to the skill capabilities chosen in the research as well as the small number of trainingunits, which leads to inconsistency with the requirements and training of physical and skill performance andthe type of muscular work to perform. Hence, the research problem crystallized, as the researcher decided tostudy this topic and prepare special exercises to develop some physical and skill capabilities using auxiliarytools to develop and their impact on the performance of two-point hopping by basketball players for (3 vs3) for youth.